Incidental thyroid tumour during surgical tracheostomy in a patient with toxic epidermal necrolysis. Issue 2 (April 2022) - Hurley, Ciaran M.; Phoenix, Eimear; Duff, Gerald; Lennon, Paul; Shelley, Odhran P.
Highlights: Toxic epidermal necrolysis is a severe cutaneous adverse inflammatory reaction. This is a case report of a 35 year-old-male with acute TEN who required a surgical tracheostomy for prolonged intubation needs. A rare finding of an incidental papillary carcinoma tumour was identified during the dissection. This has not been previously reported, and serves as a reminder of this rare and unexpected finding. Abstract: Toxic epidermal necrolysis (TEN) is a severe cutaneous adverse inflammatory reaction resulting in skin sloughing at the dermal-epidermal junction with associated mucositis. This inflammation may affect the mucosal surfaces of the respiratory, gastrointestinal, and genitourinary tracts. The extent of total body surface area and mucosal involvement has been shown to be concordant with required length of mechanical ventilation. Therefore, early tracheotomy may be indicated in patients with significant oropharyngeal mucosal involvement and incremental progression of disease. We describe the case of a 35 year-old-male with acute TEN who required a surgical tracheostomy for prolonged intubation needs. A rare finding of an incidental papillary thyroid carcinoma tumour was identified during the dissection. To the authors knowledge, this is the first report of an incidentaloma identified during a surgical tracheostomy. This report serves as a reminder to the unsuspecting burns surgeon of this rare, unexpected and likely under reported circumstance.